Contact Between 3D Beams with Deformable Circular Cross-Sections – Numerical Verification - KAWA, Olga; LITEWKA, Przemyslaw; STUDZIŃSKI, Robert (Engineering Transactions, 2018)
In this paper a numerical analysis of contact between three-dimensional elastic beams with deformations at the contact zone is carried out. The authors propose a new model of beam-to-beam contact which is the continuation of ideas presented in [6, 7, 10]. The results of beam-to-beam contact analysis are compared with the ones for full 3D problem solved in the abaqus/enviroment. The aim of the conducted numerical simulations was to select the most appropriate 3D model and to use it as a reference to verify the accuracy of the proposed beam-to-beam contact definition. The verifications were carried out for contact between beams with circular cross-sections. The obtained contact forces and the displacements of beams tips for different beams arrangements and boundary conditions showed a satisfactory correlation.